Synthesis, Characterization and Antibacterial Activity of Mixed Ligand Complexes of Pd(II) Ions with Oxalic Acid and Heterocyclic Amines (Bangladesh Pharmaceutical Journal, 2015)
The present work has been designed for the characterization and antibacterial studies of mixed ligand complexes of Pd(II) ions with phthalic acid and heterocyclic amines. The general formula of the complexes is (MLL/) [where, M = Pd(II); L = Oxalic acid, C2O4, L/ = Quinoline, C9H7N(1); iso-Quinoline, C9H7N(2)]. The complexes were prepared in the solid form and characterized by elemental analysis, conductivity & magnetic measurements and infrared & electronic spectroscopic studies. The infrared spectra of the complexes confirmed the coordination of metal ion with ligands. Their antibacterial activity has been evaluated by the disc diffusion method against seven pathogenic bacteria (three gram positive and four gram negative). The complexes were shown to exhibit mild to moderate antibacterial activity against the tested bacteria. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22314 Bangladesh Pharmaceutical Journal 17(1): 46-50, 2014